FINANCIAL INSTITUTIONS AS LEVER TEXTILES ENTERPRISE DEVELOPMENT IN LIMA - Salcedo Guzmán, Luisa Elena (2012)
The following is a study that resulted from the major weaknesses the textile sector confronts in order to have access to credit because they are considered high-risk companies. The textile sector has structural weakness since they have to compete with Asian product, which some of the even enter the Peruvian market with prices considered as DUMPING, making it even more difficult to improve the production process and to optimize the utility of its resources The objective of this study is to analyze the structure and characteristics of the textile sector of the micro companies and the evaluation of its grade of correlation with its financial sector and non-financial sector, with that in mind we have realized a real word survey that allowed us to evaluate the perception of the micro company owner with respect to the dynamic of the current sector. The population constitutes a universe of 25938 small companies of the textile sector in Metropolitan Lima and the sample of the study is 246. The selection of Lima as the place to study is due to the high concentration of textile companies and confections in the city. The results that are more outstanding are presented in the investigation and some recommendations for the major access of credit from PYMES